Transformation of Turkey's Anti-Terrorism Policy under the AKP - V. A. Avatkov; A. I. Sbitneva (Vestnik MGIMO-Universiteta)
In the era of new challenges and threats, the most dangerous of which has occurred terrorism, the Republic of Turkey becomes one of the key centers of power in the Middle East and pursues the goal to create a regional security architecture around itself as well as to counter various terrorist organizations. The aim of the research is to scrutinize the peculiarities of Ankara's anti-terrorism policy both – inside and outside the country – and its political and legal approaches to understanding the phenomenon of terrorism and methods of its combating.The study of Russia and Turkey's aspects of interaction is of particular importance. This issue seems to be especially relevant in the scope of strengthening of Russian-Turkish cooperation in recent years including the field of combating terrorism, ensuring global and regional security, and maintaining international stability. As a result of quantitative content analysis of President R.T. Erdogan's public speeches and the use of general scientific research methods, the authors conclude that the fight against terrorist threat, especially the so-called "Kurdish terrorism", is a matter of great importance for the country's leadership. At the same time Turkey's anti-terrorist activity has certain specifics and is characterized by Ankara's desire to lead anti-terrorist missions in different parts of the world and using a predominantly militaristic approach to solving the problem. This approach primarily consists in conducting cross-border anti-terrorist military operations on the neighboring states' territories. However, the military campaigns that have become an integral part of Turkey's anti-terrorism policy in many respects do not contribute to the demolishing of terrorist elements. Instead of that such operations on the contrary become an extra destabilizing factor in the Middle East. Besides that, due to the peculiarities of Turkey's interpretation of the concept of "terrorism" and its policy's implementation, Ankara's foreign anti-terrorism actions in most cases are limited to the realization of its own interests but not to achieving the goals set within the framework of the ongoing campaigns.